Prevalence of chronic pain in a metropolitan area of a developing country: a population-based study - Leão Ferreira, Karine A. S.; Bastos, Telma Regina P. D.; Andrade, Daniel Ciampi de; Silva, Aline Medeiros; Appolinario, José Carlos; Teixeira, Manoel Jacobsen; Latorre, Maria do Rosário Dias de Oliveira (Arquivos de Neuro-Psiquiatria, 2016)
To estimate the prevalence of chronic pain (CP) in the adult population living in the city of São Paulo, Brazil, and to identify factors associated with CP in developing countries.A cross-sectional study using a computer-assisted telephone interview in a two-stage stratified sample of adults living in households.2,446 subjects were interviewed. The mean age was 39.8 years old. The majority was female and 42.7% had less than 10 years of education. The prevalence of CP was 28.1%. The independent factors associated with CP were female gender (OR = 2.0; p < 0.001), age older than 65 years (OR = 1.4; p = 0.019) and less than 15 years of education (OR = 1.3-1.6; p < 0.04).The prevalence of CP was high and similar to that which has been reported in developed countries. These results raise awareness about CP and may potentially help clinicians and policy makers to design better health care programs for CP treatment in these populations.
Keywords: chronic pain; population; prevalence; developing countries